Analisa Kelayakan Pembangunan Perumahan Romansa Regency di Karanganyar Ditinjau Dari Segi Ekonomi dan Finansial - Hananto, Taufik (2016)
With increasing population and increasing standards of living, resulting in the need for higher residential house into a very important requirement. Property developments increased in Karanganyar especially residential houses resulted in the demand for land has increased, whereas the dwindling supply of land so that land prices in Karanganyar becomes higher. On investment projects, generally require substantial funds and influence the company in a fairly long period of time, therefore the necessary investment feasibility study to be careful to avoid a loss of investment in a project. No fewer investment projects are forced to stop due to lack of precise analysis of a project. So prior to the implementation of a project, a feasibility analysis is needed to determine the feasibility and value of investments in order to obtain the conclusion that the project is feasible and profitable. From the results of the analysis obtained by the Net Present Value of Rp 700 679 674; NPV> 0 (investment is acceptable). The rate of return (IRR) of 147.6%; IRR> 17% (investment worth). Benefit cost ratio of 1.22> 1 (investment worth). The payback period fixed cash flow was 19 months and 15 days, and the period of repayment with the cash flow is not fixed for 16 months of 27 days., Investment age of 24 months, so the investment is worth it. Return on investment before tax of 4.73% per month or 56.76% per year and a return on investment after tax of 4.17% per month or 50.04% per year. Break event point occurs at the time of sale of the building reaches 18 units of a total of 29 units (investment worth). Based on the above results it can be concluded that the housing project is financially feasible.